Judo performance: kinanthropometric importance for technical tactical and biomechanics - Brito, C. J.; Aedo-Muñoz, E.; Miarka, B. (Revista Brasileira de Cineantropometria e Desempenho Humano, 2020)
In such a competitive combat sport as judo, it is important that the training is carefully planned so that the athlete can stand out in the international competition. In this context, it is important that the trainer and evaluator are accurate regarding the measures taken of the athlete. Such measures, when correctly performed, can prepare the trainer with tools that allow prescribing contextualized training. The present point of view will show how kinanthropometric variables can be considered by coaches and evaluators when performing technical-tactical and biomechanical analysis in judo athletes. There are differences between sex and weight divisions as to the actions that are prevalent in each one of the categories. Lighter divisions performances must have specific training regarding approach and gripping. Attention should be paid to anticipation in athletes of the light and middle divisions. The rating of force development is the most important biomechanical measure.